ABOUT THE DIAGNOSIS OF POULTRY NEWCASTLE DISEASE - Shapulatova Zumrat Jaxongirovna; Raximov Odilbek Rakhmatullaevich; Bobomurodov Rustam Ismail o‘g‘li (European Journal of Agricultural and Rural Education, 2022)
This article provides information about the Newcastle disease of birds, pathogen, epizootology, clinical signs, pathoanatomical changes that are important in the preliminary diagnosis of the disease, the importance of timely and accurate diagnosis in the prevention of the disease, and highlights that the final diagnosis is based on the results of laboratory tests. Information is provided on the use of serological diagnostics, IFT, PCR.